Editorial Islamic Value-Based Instructional Technology Integration (IVBITI) dalam Pembelajaran Pendidikan Agama Islam: Studi Kasus di MTs Miftahul Ulum Denpasar - Agus hartanto; Masrur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has fundamentally reshaped educational practices, including Islamic Religious Education (IRE). Although instructional technology is increasingly adopted, its implementation in Islamic schools remains challenged by disparities in teachers' digital competence, limited infrastructure, and insufficient alignment between technology, pedagogy, and Islamic values. Previous studies have predominantly examined the effectiveness of specific digital media using quantitative approaches, leaving limited understanding of how instructional technology is comprehensively integrated into IRE learning. This study aims to analyze the forms of instructional technology integration, its contribution to students' learning outcomes, and the supporting and inhibiting factors influencing its implementation at MTs Miftahul Ulum Denpasar. A qualitative case study design was employed. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña involving data condensation, data display, and conclusion drawing, supported by source and method triangulation. The findings reveal that instructional technology integration is implemented systematically through instructional planning, classroom implementation, and learning evaluation by utilizing digital media aligned with Islamic Religious Education content and learners' characteristics. The integration contributes to improved cognitive achievement, student engagement, digital literacy, and religious character development. Furthermore, this study proposes the Islamic Value-Based Instructional Technology Integration (IVBITI) model, integrating digital leadership, teachers' technological pedagogical competence, Islamic instructional design, meaningful digital learning experiences, and continuous improvement cycles. The proposed model contributes theoretically to Islamic educational technology and provides a practical framework for Islamic schools in designing effective technology-enhanced Islamic Religious Education.